PENGARUH STRES KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP INTENTION TO QUIT KARYAWAN PADA PT. BPR TISH BATUBULAN - Yogi Pratiwi, Intan; Ardana, I Komang (E-Jurnal Manajemen; Vol 4 No 7 (2015), 2015)
ABSTRACT There are several factors that led to the desire of employees to leave the company, one of which is the job stress and organizational commitment. Frequent occurrence of intention to quit very direct impact on the company. The purpose of this study was to determine the effect of work stress and organizational commitment to the intention to quit. The study, titled "The Effect of Job Stress and Organizational Commitment Of Intention To Quit Employees at PT BPR Tish research design associative causal relationship with a sample of 35 people. Methods of data collection, observation, interviews, and questionnaires. The data analysis technique used is multiple regression analysis, the classical assumption test, regression test simultaneously (Ftest),  and partial regression test ) (ttest). Based on the results of analysis show that work stress variables and organizational commitment significant effect partially and simultaneously to the intention to quit employees on PT.BPR Tish in Batubulan. The implication of this study is to strengthen the previous theory, the formation of the theoretical basis of behavior used in conjunction with the intention to quit the behavior is influenced by factors of job stress and organizational commitment
Keywords: job stress, organizational commitment, intention to quit